The expression is given to be:
![(a^2-36)/(5a+30)](https://img.qammunity.org/2023/formulas/mathematics/college/ioggqtq4a7xofn564n0dzidkaf60u1vtpp.png)
From the numerator, using the difference of two squares, we have:
![a^2-36=a^2-6^2=(a-6)(a+6)](https://img.qammunity.org/2023/formulas/mathematics/college/l8f8g2n7ad3wvv2zr51y6cwaih3rwxakv4.png)
From the denominator, by factorization, we have:
![5a+30=5(a+6)](https://img.qammunity.org/2023/formulas/mathematics/college/wi7ge9ltr1fb11bv3v3h0pzeshwwpqswwi.png)
Therefore, the expression becomes:
![\Rightarrow((a-6)(a+6))/(5(a+6))](https://img.qammunity.org/2023/formulas/mathematics/college/fmsz5t6tu7igf96311fckewv3zyn8lek1t.png)
Cancel out common terms in the denominator and numerator. The simplified expression will be:
![\Rightarrow(a-6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/6j5wsawokyy5rz6zh77n3qaxmmlhooxcxb.png)
From the original expression, the variable restriction will be at:
![\begin{gathered} 5a+30=0 \\ Solving \\ 5a=-30 \\ a=-(30)/(5) \\ a=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qc1j4mtzapkqsgpnr3t16yvtp6gjckk778.png)
The restriction is:
![-6](https://img.qammunity.org/2023/formulas/mathematics/college/o08oc32y1tdfy3t4ef303j64rf1ovu0ni6.png)